Effect of attachment-based family therapy to reduce depression among persons diagnosed with schizophrenia - S, Sivapriya; K, Mahalakshmi (Journal of Associated Medical Sciences, 2024)
Background: Schizophrenia is a chronic mental disorder that affects a person’s way of thinking, his behaviors, and his or her feelings. One of the common symptoms of schizophrenia is depression, and depression can be associated with suicidal thoughts. Attachment-based family therapy is an intervention that was used to treat depression in young adults but has never been used in persons diagnosed with schizophrenia Objective: This study was done to find out the effect of Attachment-based family therapy on reducing depression among persons diagnosed with schizophrenia. Materials and methods: Thirty male participants aged between 25 and 60 years who were already diagnosed with schizophrenia were selected and participated in this study. The participants were divided into 2 groups, with 15 participants in each as experimental and control groups. Beck’s Depression Inventory was used to find out the level of depression in both groups. The experimental group underwent Attachment-Based Family Therapy, whereas the control group attended conventional occupational therapy for 3 months. The SPSS software version was used for data analysis. The descriptive statistics examined the distribution of records to summarize the data. If the p<0.05, it is statistically significant.> <0.05, it is statistically significant. Results: The results of this study showed that Attachment-Based Family Therapy was effective in reducing depression among persons diagnosed with Schizophrenia. Conclusion: The results suggested that Attachment-Based Family Therapy was effective for the experimental group, and the level of depression decreased after the intervention.